Rapid diagnostic pathways for suspected colorectal cancer: views of primary and secondary care clinicians on challenges and their potential solutions. Issue 10 (22nd October 2015) - Redaniel, Maria Theresa; Ridd, Matthew; Martin, Richard M; Coxon, Fareeda; Jeffreys, Mona; Wade, Julia
Abstract : Objectives: To ascertain the challenges associated with implementation of the 2-week wait referral criteria and waiting time targets for colorectal cancer and to identify recommendations for improvements to the pathway. Design: Qualitative research using semistructured interviews and applying thematic analysis using the method of constant comparison. Setting: 10 primary care surgeries and 6 secondary care centres from 3 geographical areas in the England. Participants: Purposive sample of 24 clinicians (10 general practitioners (GPs), 7 oncologists and 7 colorectal surgeons). Results: GPs and specialists highlighted delays in patient help-seeking, difficulties applying the colorectal cancer referral criteria due to their low predictive value, and concerns about the stringent application of targets because of potential impact on individual care and associated penalties for breaching. Promoting patient awareness and early presentation, clarifying predictive symptoms, allowing flexibility, optimising resources and maximising care coordination were suggested as improvements. Conclusions: Challenges during diagnosis and treatment persist, with guidelines and waiting time targets producing the perception of unintended harms at individual and organisational levels. This has led to variations in how guidelines are implemented. These require urgent evaluation, so that effective practices can be adopted more widely.